Middle range theory for the nursing diagnosis Excess Fluid Volume in pregnant women - Nathaly Bianka Moraes Fróes; Marcos Venícios de Oliveira Lopes; Cleide Maria Pontes; Gabriele Lima Ferreira; Priscila de Souza Aquino (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To stablish a middle range theory for the understanding of the causal mechanisms and clinical consequentes of the nursing diagnosis Excess Fluid Volume (00026) among pregnant women. Method: The Middle Range Theory was constructed in five stages: defining of construction approach, establishing main concepts, elaborating propositions, developing a pictorial diagram, and establishing the causal relationships and evidence for practice of the Middle Range Theory. Results: We identified 14 clinical indicators and 6 causal factors of Excess Fluid Volume. A pictorial diagram was developed and relationships between Excess Fluid Volume elements were established with 6 propositions for them. Conclusion: The Middle Range Theory included both physiological and pathological conditions to explain Excess Fluid Volume. This Middle Range Theory might help in the better understanding of interactions between causal factors and clinical indicators of Excess Fluid Volume.